Development and Implementation of Multiplex TaqMan Array Cards for Specimen Testing at Child Health and Mortality Prevention Surveillance Site Laboratories - Diaz, Maureen H (Clin Infect Dis, 2019)
Child Health and Mortality Prevention Surveillance (CHAMPS) laboratories are employing a variety of laboratory methods to identify infectious agents contributing to deaths of children <5 years old and stillbirths in sub-Saharan Africa and South Asia. In support of this long-term objective, our team developed TaqMan Array Cards (TACs) for testing postmortem specimens (blood, cerebrospinal fluid, lung tissue, respiratory tract swabs, and rectal swabs) for >100 real-time polymerase chain reaction (PCR) targets in total (30–45 per card depending on configuration). Multipathogen panels were configured by syndrome and customized to include pathogens of significance in young children within the regions where CHAMPS is conducted, including bacteria (57 targets covering 30 genera), viruses (48 targets covering 40 viruses), parasites (8 targets covering 8 organisms), and fungi (3 targets covering 3 organisms). The development and application of multiplex real-time PCR reactions to the TAC microfluidic platform increased the number of targets in each panel while maintaining assay efficiency and replicates for heightened sensitivity. These advances represent a substantial improvement in the utility of this technology for infectious disease diagnostics and surveillance. We optimized all aspects of the CHAMPS molecular laboratory testing workflow including nucleic acid extraction, quality assurance, and data management to ensure comprehensive molecular testing of specimens and high-quality data. Here we describe the development and implementation of multiplex TACs and associated laboratory protocols for specimen processing, testing, and data management at CHAMPS site laboratories.